Etyka w ekonomicznych badaniach naukowych - Wyżnikiewicz, Bohdan (Annales. Etyka w Życiu Gospodarczym, 2008)
The paper summarizes the author’s experience of conducting economic scientific research.Economic scientific research is understood as both an analysis of economic phenomena and researchpurchased on the market of research services. The former are not subject to ethical dilemmas. It is aprofessional approach backed by sound economic theory that is important.The latter, regardless of who purchases research services, pose a risk of ethical dilemmas andconflicts of interest. The area of potential risk is connected to expectations of organizations purchasingresearch services. In most cases organizations are interested to receive objective assessments orrecommendation necessary to take decisions.Ethical conflict appears when the destination of research is lobbing or a company’s imagecreation. The results of research may be used as an instrument of competition.It is thus vital that a research organization should judge the ethical dimension of undertakenresearch tasks. Research projects being socially beneficial should be definitely undertaken. Incontroversial cases, the conviction of the rightfulness in the ethical dimension ought to be decisive. Inall cases the principal rule should be aiming at achieving scientifically objective assessments andopinions.